The Effect of Reflective Thinking on Critical Thinking Skills: A Predictive Analysis - Firdaus, Laras; Samsuri, Taufik; Mirawati, Baiq (Empiricism Journal, 2024)
University students must possess reflective and critical thinking skills to effectively navigate various life situations and contexts. This study aims to explain the effect of reflective thinking skills (RTS) on critical thinking skills (CTS). In this study, 71 prospective biology teacher students voluntarily participated. The RTS instrument developed by Kember et al. (2000) was adopted to collect data on RTS, and 20 CTS items to collect data on CTS. RTS had a significant impact on CTS, but not all RTS subscales; the habitual action subscale did not have a significant impact on CTS. Additionally, semester differences did not influence RTS and CTS. Finally, the recommendations based on these findings can be found in the conclusions and recommendations section.